ANTIOXIDATIVE ACTIVITY OF UGANDAN MEDICINAL PLANTS - Kuglerova, M.; Marsik, P.; Vanek, T.; Kokoska, L.; Wanyana-Maganyi, O.; Van Damme, P.; Grade, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plant drugs used in African traditional medicine are important source of compounds with various biological activities [1]. For the specific situation of Uganda, there is little information on medicinal plant use by traditional healers in Karamoja region (north-east Uganda). Moreover, even though there are some reports on pharmacology of Ugandan medicinal plants [2], their antioxidative activities are still poorly documented. Thus we decided to investigate antioxidative activity of seven Ugandan tree species selected according to their use in traditional medicine as evidenced by ethnobotanical research. The crude ethanolic extracts of seven barks traditionally used by Karamojong healers, namely Capparis tomentosa (Capparaceae), Dregea rubicunda (Asclepiadaceae), Fagaropsis angolensis (Rutaceae), Trichilia prieuriana (Meliaceae), Turraea floribunda (Meliaceae), Warburgia ugandensis (Canellaeceae), and Zanthoxylum chalybeum (Rutaceae) was tested for antioxidative activity using 2,2-diphenyl-1-picrylhydrazil (DPPH) free radical scavenging assay. The most promising results showed extract of W. ugandensis, which exhibited DPPH scavenging activity with IC50 value (7 µg/ml) very closed to the effect achieved by reference compounds Trolox (IC50= 4 µg/ml) and ascorbate (IC50= 2 µg/ml). Among the other plants tested, Z. chalybeum, F. angolensis and T. prieuriana exhibited certain antioxidative potential with IC50 values of 23 µg/ml, 175 µg/ml and 377 µg/ml, respectively. C. tomentosa, D. rubicunda and T. floribunda showed no free radical scavenging activity in the assay. Acknowledgements: Czech Ministry of Education, Youth and Sports (Project No. 6046070901 and ME08070). References: 1.Katerere, D.R. et al. (2003) Phytochemistry 63:81-88. 2. Katuura, E. et al. (2007) Afr J Ecol 45:48-51.